Prediction of Response in Head and Neck Tumor: Focus on Main Hot Topics in Research - Belgioia, Liliana; Morbelli, Silvia Daniela; Corvò, Renzo (Frontiers in Oncology, 2021)
Radiation therapy is a cornerstone in the treatment of head and neck cancer patients; actually, their management is based on clinical and radiological staging with all patients at the same stage treated in the same way. Recently the increase knowledge in molecular characterization of head and neck cancer opens the way for a more tailored treatment. Patients outcomes could be improved by a personalized radiotherapy beyond technological and anatomical precision. Several tumor markers are under evaluation to understand their possible prognostic or predictive value. In this paper we discuss those markers specific for evaluate response to radiation therapy in head and neck cancer for a shift toward a biological personalization of radiotherapy.